Determining the title to appear before court in cases of indemnity for damages caused to patients - Stępniak, Piotr (Journal of Medical Science, 2017)
The issue of the title to appear before court mentioned in the title, is poorly known both to patients and to medical staff, in particular to doctors. However, in practice this is very important because of the growing number of cases of this type pending before the regional medical adjudication committees, as well as common courts. For that reason, it is worth discussing legal regulations in this field. This is also the purpose of the author of this publication.